Combination therapy accelerates diabetic wound closure. - Robert J Allen; Marc A Soares; Ilyse D Haberman; Caroline Szpalski; Jeffrey Schachar; Clarence D Lin; Phuong D Nguyen; Pierre B Saadeh; Stephen M Warren (PLoS ONE, 2014)
Non-healing foot ulcers are the most common cause of non-traumatic amputation and hospitalization amongst diabetics in the developed world. Impaired wound neovascularization perpetuates a cycle of dysfunctional tissue repair and regeneration. Evidence implicates defective mobilization of marrow-derived progenitor cells (PCs) as a fundamental cause of impaired diabetic neovascularization. Currently, there are no FDA-approved therapies to address this defect. Here we report an endogenous PC strategy to improve diabetic wound neovascularization and closure through a combination therapy of AMD3100, which mobilizes marrow-derived PCs by competitively binding to the cell surface CXCR4 receptor, and PDGF-BB, which is a protein known to enhance cell growth, progenitor cell migration and angiogenesis.Wounded mice were assigned to 1 of 5 experimental arms (n = 8/arm): saline treated wild-type, saline treated diabetic, AMD3100 treated diabetic, PDGF-BB treated diabetic, and AMD3100/PDGF-BB treated diabetic. Circulating PC number and wound vascularity were analyzed for each group (n = 8/group). Cellular function was assessed in the presence of AMD3100. Using a validated preclinical model of type II diabetic wound healing, we show that AMD3100 therapy (10 mg/kg; i.p. daily) alone can rescue diabetes-specific defects in PC mobilization, but cannot restore normal wound neovascularization. Through further investigation, we demonstrate an acquired trafficking-defect within AMD3100-treated diabetic PCs that can be rescued by PDGF-BB (2 μg; topical) supplementation within the wound environment. Finally, we determine that combination therapy restores diabetic wound neovascularization and accelerates time to wound closure by 40%.Combination AMD3100 and PDGF-BB therapy synergistically improves BM PC mobilization and trafficking, resulting in significantly improved diabetic wound closure and neovascularization. The success of this endogenous, cell-based strategy to improve diabetic wound healing using FDA-approved therapies is inherently translatable.